2018
DOI: 10.1002/srin.201800071
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Electromagnetic Field, Fluid Flow, and Solidification in a Bloom Continuous Casting Mold by Numerical Simulation

Abstract: Based on the Maxwell's equations and low‐Reynolds number k−ϵ turbulence model, a coupled three‐dimensional numerical model has been developed to describe the electromagnetic field, fluid flow, and solidification in a bloom continuous casting mold with electromagnetic stirring (M‐EMS). The optimum frequency is obtained by calculating the maximum electromagnetic torque of the strand with consideration of mold tube shield effect. The effect of stirring current intensity on the turbulent flow, temperature distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…Since the magnetic induction intensity during continuous casting process can not be measured, most of the researchers [8,[10][11][12][13][14] verify their mathematical models of continuous casting process with M-EMS by comparing the calculated and measured magnetic induction intensities without casting steel. Therefore, to verify the validity of the established models, the calculated and measured magnetic induction intensities without casting steel are shown in Figure 2.…”
Section: Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the magnetic induction intensity during continuous casting process can not be measured, most of the researchers [8,[10][11][12][13][14] verify their mathematical models of continuous casting process with M-EMS by comparing the calculated and measured magnetic induction intensities without casting steel. Therefore, to verify the validity of the established models, the calculated and measured magnetic induction intensities without casting steel are shown in Figure 2.…”
Section: Model Validationmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Trindade et al [8] reported the inclusion trajectory and removal law by coupling magnetic field, flow field, and particle transport. [8][9][10][11][12][13][14][15] Trindade et al [8] reported the inclusion trajectory and removal law by coupling magnetic field, flow field, and particle transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu and Zhu [8] simulated the flow field, the distribution of the temperature field, and the inclusion trajectory in the round billet, and conducted an industrial test to adjust the stirring parameters of the M-EMS, which significantly improved the shrinkage and surface defects of the strand. Li et al [9,10] established a coupled model of electromagnetic, flow, heat transfer, and solidification under the low Reynolds number model of bloom casting. The electromagnetic field under different stirring parameters was revealed, and it was seen that increasing the current intensity will not only promote superheat dissipation, but also cause slow growth in the region of shell solidification.…”
Section: Introductionmentioning
confidence: 99%
“…Wall surface: a non-slip wall surface is adopted and the nozzle wall is set to adiabatic. The heat flux boundary condition is applied on the mold zone according to Li [10]:…”
mentioning
confidence: 99%